Communication in French Foreign Language Learning by Implementing the Aspects of Interculturality - Birova, Jana; Vasbieva, Dinara G.; Masalimova, Alfiya R. (Communications - Scientific Letters of the University of Zilina, 2017)
This research paper examines the case study and the weak sides of the implementation of intercultural education in a FLT class, and then examines how such teaching could be effective. The didactic intervention through which the native teacher was reflexive was done in two stages in order to recover all the didactic aspects necessary for a successful implementation in the future.
Keywords: interculturality; aspects; french; teaching; process; communication